Intravesical Tension-Free Vaginal Tape Removal: Is There a Single Solution?. (6th March 2011) - Zakri, Rhana H.; Patel, Amit K.; John, Babbin S.; Shrotri, Nitin C.
Abstract : Stress urinary incontinence (SUI) affects 10–20% of women in the general population. Surgery for stress incontinence has been performed on women for over a century, but with the advent of new urogynaecological sling procedures for its management, urological surgeons are having to deal with an increasing number of patients presenting with associated complications. With no clarity on the full range of possible complications or certain consensus on their optimal management, the ideal treatment remains a decision for the individual surgeon. In view of this, we felt it of common interest to review the literature for the history of sling procedures, present commonly arising complications, and seek to answer the question in the title.